Hydrogen assisted cracking resistance test to evaluate the hydrogen service for 2.25Cr-1Mo-V steel heavy wall hydroprocessing reactors - Akitada YASUTOMI; Yuta HONMA; Mitsuru OHATA (Nihon Kikai Gakkai ronbunshu)
It has been about 25 years since petroleum refining reactors used in hydrocracking and hydrodesulfurization process have been made of 2.25Cr-1Mo-V (F22V : SA-336(M)-F22V) steel. The F22V steel reactors are expected to operate continuously for decades, thus are required to have high reliability to withstand the high-temperature, high-pressure hydrogen environments. Although the assessments of minimum pressurization temperature (MPT) and remaining life of in-service reactors are required for efficient plant management, it is unclear whether the impact properties required for weld metals in the materials and fabrication standard such as API 934-A provide sufficient toughness for hydrogen assisted cracking (HAC) resistance in the welded joints of reactor under hydrogen service. It means that it is not clear how to deal with the assessments of MPT and remaining life of in-service reactors. Therefore, in this study, based on the results of finite element method (FEM) simulations of temperature, stress and hydrogen concentration distributions generating in the reactor wall under service, the HAC influence factors in each stage that is classified into startup, steady-state operation and shutdown were extracted. We then investigated the test method and conditions that simulated these influence factors for evaluating the HAC resistance in each stage of reactor operation. Furthermore, the HAC resistance tests using the welded test plate simulating the girth weld joint of actual reactor were conducted, and its characteristics were evaluated with the focus on the resistance to HAC initiation. In conclusion, the threshold stress intensity factor for HAC initiation, KIH measured in the HEAC resistance test under reactor startup conditions was conservative, and it was found that the possibility of HAC initiation during reactor operation (KI ≥ KIH), i.e., the MPT for reactor to prevent it, can be evaluated by the HEAC resistance test under reactor startup conditions.